“Atributos de calidad del servicio y la satisfacción del paciente en la Clínica Limatambo Cajamarca SAC, 2016” - Saldaña Perez, Elmer Miguel (2020)
ABSTRAC The main objective of the research is to analyze the attributes of service quality and level of patient satisfaction at the Limatambo Cajamarca SAC Clinic in 2016. The research design selected for the application and verification of the hypothesis corresponds to the non-experimental studies and the correlational descriptive type. The population was made up of 3552 patients and the sample was 150 patients, probabilistically selected. For the collection of information, a questionnaire was used to evaluate the variable attributes of service quality and another questionnaire to evaluate patient satisfaction. The hypothesis was tested by applying the Pearson's non-parametric statistical test whose results show that there is a significant relationship (r = 0.201) between the attributes of the quality of service and the degree of patient satisfaction at the Limatambo Cajamarca SAC Clinic, in 2016: that is, the higher quality attributes the greater the customer satisfaction. In addition, the results show that the satisfaction averages of the evaluated factors are above 60% and the perception of the quality of service attributes has averages above 50%. Likewise, although the results obtained in the research are positive in terms of satisfaction levels and the perception of quality attributes, it does not have a defined strategy that allows it to generate levels of satisfaction that are sustainable over time and thus generate a competitive advantage over its competitors. That is why a plan was drafted in order to improve and make satisfaction levels sustainable by reducing weaknesses and taking advantage of market opportunities to build customer loyalty.